HUBUNGAN TINGKAT PENGETAHUAN ANGGOTA IDI TENTANG KODE ETIK KEDOKTERAN TERHADAP SIKAP UPAYA PENCEGAHAN TINDAKAN ABORSI ILEGAL - Chantika Zahra Adisaputra (2022)
Illegal Abortion is the deliberate termination of a pregnancy without a valid medical reason. Each year, the number of illegal abortions increases. This event cannot be divorced from the medical profession, which has professional criteria compiled by the IDI Organization. These guidelines are known as the Indonesian Code of Medical Ethics and serve as a guideline for various health services and procedures, including Abortion. This study examined South Jakarta IDI members' KODEKI knowledge and attitudes toward illegal abortion prevention. Observational analysis with a cross-sectional design constitutes the study methodology. The research sample that matched the inclusion requirements comprised 96 IDI residents in South Jakarta selected using a simple random selection procedure. The findings of this study's univariate analysis revealed that the majority of the sample consisted of females, that the majority of the participants were between the ages of 26 and 35 (early adulthood), that participants possessed sufficient information about KODEKI, and that the majority of participants had a high level of awareness regarding the prevention of illegal abortions. Chi-square was utilized to examine this study. The findings of the chi-square test revealed no association between awareness of KODEKI and attitudes and attempts to prevent illicit abortions (p = 0.904). Thus, South Jakarta IDI members' attitudes toward preventing illegal abortions are unrelated to their understanding of the medical code of ethics understanding. This illustrates that information does not completely change a person's mindset because other things can too.